White Paper on Joint Replacement: Status of Hip and Knee Arthroplasty Care in Germany - Miriam Kip (Springer Nature, 2017)
This White Paper details the status of hip and knee arthroplasty care in Germany. Hip and knee replacements are amongst the most frequently performed procedures and usually become necessarily due to age-related wear of the joint, osteoarthritis and fractures of the femoral neck. In light of demographic change, demands with regard to standards of care and the procedures are likely to rise. This book addresses people involved in shaping and representing the healthcare system from a variety of fields including medical professions, health insurances and health sciences as well as journalists and patient representatives.